Analisis Pengaruh Layer Height dan Printing Speed pada Proses FDM Terhadap Kekuatan Mekanik Filamen PETG - Pristiansyah Pristiansyah; Luthfi Maulana Alvianto; Soni Afriansyah; Zaldy Sirwansyah Suzen (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The rapid development of manufacturing technology is marked by the emergence of Additive Manufacturing (AM) or 3D Printing technology. This study aims to analyze the effect of layer height and printing speed on the mechanical strength of PETG material using the Fused Deposition Modeling (FDM) method. The printing process was carried out using an Ender 3 Pro 3D printer with process parameter variations of layer height (0.2, 0.3, and 0.4 mm) and printing speed (40, 50, and 60 mm/s) arranged according to the Taguchi L9 (3²) experimental design. eSUN PETG filament was selected due to its compatibility with the test requirements. The test specimens were fabricated according to the ASTM E23 standard with dimensions of 55 × 10 × 10 mm for impact strength testing. The results show that printing speed has a more significant influence on mechanical strength compared to layer height. The Taguchi analysis indicates that layer height contributes the most to the mechanical performance, followed by printing speed. The optimal combination was obtained at a layer height of 0.2 mm and a printing speed of 40 mm/s. Overall, the study highlights the critical role of process parameter optimization in improving the mechanical strength of 3D printed PETG thermoplastic materials.